2023
DOI: 10.4274/balkanmedj.galenos.2022.2022-7-26
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Risk Factors for Predicting Postoperative Human Serum Albumin Infusion after Hip Fracture Surgery: Development and Validation of a Nomogram

Abstract: Background: As one of the adverse events after hip fracture surgery, hypoalbuminemia is usually treated using human serum albumin infusion. However, the application of human serum albumin may cause complications such as postsurgical infection and increased mortality. Aims: To examine the preoperative risk factors of human serum albumin infusion after hip fracture surgery, establish a nomogram prediction model, and verify its accuracy. Study Design: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Third, as all subjects in this study were postsurgical inpatients and serum albumin levels were affected by surgery, surgery may have influenced the results of this study. 33) In addition, the times between the date of surgery and the bioelectrical impedance analysis and between the date of surgery and the date of the blood tests were not consistent. Performing blood tests and bioelectrical impedance analyses on the same day is likely to yield more accurate results.…”
Section: Discussionmentioning
confidence: 97%
“…Third, as all subjects in this study were postsurgical inpatients and serum albumin levels were affected by surgery, surgery may have influenced the results of this study. 33) In addition, the times between the date of surgery and the bioelectrical impedance analysis and between the date of surgery and the date of the blood tests were not consistent. Performing blood tests and bioelectrical impedance analyses on the same day is likely to yield more accurate results.…”
Section: Discussionmentioning
confidence: 97%
“…The nomogram has been accepted as a reliable tool to create a simple intuitive graph of a statistical predictive model that quantifies the risk of a clinical event 22 , 23 . Numerous studies have indicated their potential value in clinical practice 24 , 25 . The following seven variables were included in the simplified model: age, sex, length of stay, RBC transfusions, hemoglobin, platelet and eGFR.…”
Section: Discussionmentioning
confidence: 99%